Controllable synthesis of fluorescent silver nanoparticles with different length oligonucleotides - Wenhui Bao; Jun Ai; Lu Ga (IET Nanobiotechnology)
Abstract Silver nanomaterials have become important research topics in recent years. As a new type of fluorescent material, silver nanomaterials have been applied to fluorescent sensors, bioimaging and materials targeting cancer cells. Here, an approach to the oligonucleotide‐templated controllable formation of fluorescent Ag nanomaterials is reported. In this experiment, silver nanoparticles (NPs) were synthesised from oligonucleotides chains, sodium borohydride (NaBH4) and silver nitrate (AgNO3) by changing the molar ratio of DNA to sodium borohydride (NaBH4) and silver nitrate (AgNO3). Fluorescent assay and transmission electron microscopy were used to characterise the silver NPs. The optimal selection of DNA chains with different lengths as templates for the synthesis of silver NPs was found. This work successfully develops the capping oligonucleotides scaffolds of silver nanoclusters.